Anxiety of Pregnant Women and Determination of Maternity Health Care Facility during the COVID-19 Pandemic - Hilda Sulistia Alam; Sutrisna Altahira; Risnawati (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
There are physical and psychological changes during pregnancy experienced by pregnant women. Anxiety often increases before delivery, especially in the third trimester. During pregnancy, COVID-19 can contribute to a woman's mental health issues. Anxiety is often experienced regarding previous birth and delivery, fear of becoming infected with COVID-19 and transmitting it to others, and information obtained from social media regarding the susceptibility of pregnant women to COVID-19. Anxiety will impact decision making, especially concerning the selection of maternity health care facilities during the COVID-19 pandemic. This was a quantitative analytical study with cross-sectional design through survey methodology that was conducted July-November 2021 in the work area of 3 Community Health Centers (Betoambari, Katobengke and Kadolomoko) at Baubau City, Southeast Sulawesi. 72 pregnant women in the third trimester who were recorded in the MCH book were selected as the study samples through probability sampling technique. This study aims to determine the relationship between anxiety of pregnant women and the type of maternity health care facility during the COVID-19 pandemic. Data were collected using HARS (Hamilton Anxiety Rating Scale) questionnaire. The results of data analysis using the Chi-Square test obtained a p=0.001<α=0.05. There was a relationship between anxiety of pregnant women and the type of health care facility during the COVID-19 pandemic. Women with severe anxiety chose Private Practice Midwife (16.6%), women with moderate anxiety chose CHC (15.2%) and women with mild anxiety chose hospital (12.5%) as a maternity health care facility during the Covid-19 pandemic.